Construction of Binary Linear Codes from Zero Divisor Graphs - Vira Hari Krisnawati; Ardi Nur Hidayat; Muhammad Husnul Khuluq (Science and Technology Indonesia, 2026)
Binary linear codes play an essential role in communication systems by ensuring reliable data transmission. One approach to constructing binary linear codes is through graph theory. In this paper, we study the construction of binary linear codes derived from the incidence matrices of zero divisor graphs of the rings Z(pᵅ) and Z(pᵅqᵝ), where p, q are prime numbers and α, β ≥ 1 are integers. We analyze the parameters of the resulting binary linear codes, such as their length, dimension, and minimum distance. Furthermore, we investigate some examples of the constructed codes. To justify their theoretical and practical relevance, we perform an optimality analysis comparing the constructed codes with classical bounds. All evaluated codes strictly satisfy the Hamming sphere-packing bound. This work offers a new contribution to the study of linear codes by combining ideas from algebra, graph theory, and coding theory.